Shelf-Life Assessment of Canola Protein Bio-Adhesive - Lawrence Tene Tayo; Aldo Joao Cárdenas-Oscanoa; Lizhen Chen; Darshan Shivappa Nayaka; Markus Euring (BioResources)
The storage stability of binders before their application is a crucial factor in the wood panel industry, as it impacts the mechanical properties, quality control, economic efficiency, and market competitiveness of the final products. In the present study, the long-term stability of two canola protein isolate (CPI) and two canola meal (CM) adhesive variants was investigated. The protein-based adhesives were prepared and tested on one-layer particleboards after one week, one month, two months, three months, and four months of storage of the formulations. Results indicate that the CPI-based outperformed the CM-based variants in terms of internal bonding strength (IB), modulus of rupture (MOR), and modulus of elasticity (MOE) due to the higher protein concentration of the CPI over the CM. While the IB strength of the CM-bonded particleboards was lower than the EN 319 requirement after the first four weeks of storage (0.34 N/mm2 and 0.29 N/mm2 for nitrite and bisulfate-crosslinked respectively), that of the CPI-bonded was still superior to the EN 319 after four months (0.44 N/mm2 and 0.3 N/mm2 for nitrite and bisulfate-crosslinked respectively). This indicates that the nitrite-crosslinked variants had a more robust chemical formulation, leading to stronger and more durable bonds.